Frontiersmen in Blue : the United States Army and the Indian, 1848-1865 - Utley, Robert M., 1929-2022 (University of Nebraska Press, 2014)
Frontiersmen in Blue is a comprehensive history of the achievements and failures of the United States Regular and Volunteer Armies that confronted the Indian tribes of the West in the two decades between the Mexican War and the close of the Civil War. Between 1848 and 1865 the men in blue fought nearly all of the western tribes. Robert Utley describes many of these skirmishes in consummate detail, including descriptions of garrison life that was sometimes agonizingly isolated, sometimes caught in the lightning moments of desperate battle.